The Development of Tourist’s Motivation towards Tourism in Sa Kaeo as Frontier Tourism Destination - Sainaratchai, Krittika; Kieanwatana, Komsit (Journal of Cultural Approach, 2019)
The purposes of this research were to study tourists’ behaviors in travelling and travel motivation and to develop tourism motivation in Sa Kaeo as the frontier tourism destination. The samples were 400 Thai tourists responded to the survey. Data were analyzed statistically. Results 1. Respondents were the female aged between 20–30 years old, who were undergraduate students having their salary less than 5,000 bath. 2. Respondents had traveled to Sa Kaeo for the first time with their family. Their main purpose of visiting was travelling or leisure on holidays. The Rong Kluea Market is the place that tourists had reminded and they also had thought as Sa Kaeo’s symbol. The internet was used to search for information regarding to Sa Kaeo. 3. The opinion of respondents on tourist’s motivation towards tourism in Sa Kaeo was ranked in a high level in terms of physical motivation ( = 3.56, S.D.= 0.70), culture motivation ( = 3.70, S.D.= 0.73), interpersonal motivation ( = 3.61, S.D.= 0.69), and status and prestige motivation ( = 3.58, S.D.= 0.70) respectively.